Analysis of outdoor LED lighting's dimming influence on the performance of LED drivers - Perko, Jurica (JET on-line, 2017)
With the development of new technologies, LEDs (light-emitting diodes) take a significant position in lighting due to their long-life spans and high luminous efficacy, which result in energy and maintenance cost savings. These efficient and innovative light sources require adequate ballast or electronic control gear, also known as LED drivers, for their operation. An LED driver provides appropriate voltage level and current for the operation of LEDs. It converts and rectifies higher voltages of alternating current to lower voltages of direct current and regulates the current flowing through LEDs at a nominal level. There are many advantages and disadvantages to using LEDs, primarily caused by LED circuits and LED drivers. The dimming influence of outdoor LED lighting on the LED driver performance is analysed in this paper, specifically the testing of an LED lighting driver by changing the load level. Results of LED driver efficiency calculated from measured input and output power, output voltage ripple measurements, and total harmonic distortion analysis are shown. Based on the measurement results, significant recommendations and concluding remarks are given.
Keywords: constant current driver; dimmer control; efficiency; krmilniki; LED driver; LED tehnologija; outdoor LED lighting; output voltage ripple; pulsation; razsvetljava; THDI